Students’ motivation and ownership in a cross-campus and online setting - Lysne, Dag Atle; De Caro-Barek, Veruska; Støckert, Robin; Røren, Kari Anne Flem; Solbjørg, Ole Kristen; Nykvist, Shaun Sydney (Frontiers in Education, 2023)
This study focuses on motivation and ownership of learning in team-based learning in a cross-campus and online setting. In team-based learning it is essential that students have a high level of commitment to the tasks that should be solved. However, this can be challenging when students collaborate both on campus and online across campuses. In this study we have interviewed twelve students from a joint international Master’s in Music, Communication and Technology between two large Nordic universities. The aim was to identify factors that were most likely to impact student motivation and ownership in this cross-campus and online setting. Three main themes emerged from an analysis of the findings. These were identified as important for motivation and ownership and were identified as autonomy, peer learning and communication and social bonding. The results of the study highlight the importance of having a focus on communication and social bonding should be included in the planning of the course in order for universities to succeed and transform to meet the needs of a very diverse group of future students. Future learning environments, which will be physical as well as virtual, or a mix of those, will need to focus on student tasks that should be flexible and open for student choice, and peer learning should be one of the main learning activities.